Analysis Of Internal Factors Affecting Bank Probability: Evidence From Listed Banks On Vietnam Stock Market - Dieu Nguyen, Chi Thi; Thuy Nguyen, Trang Thi (International Journal of Informatics and Information Systems, 2021)
This study using the multivariate linear regression model based on the ordinary least squares method (OLS) to estimate the internal factors affecting profitability of 9 listed banks on Vietnam Stock Market for the period from 2008 to 2016. A sample with 81 observations was used in study model, and Return on assets (ROA) is used to measure banks’ profitability in the study model. The results indicated that capital size and loan have a positive and significant effect on bank profitability, and asset size, deposits, liquidity risk and bad debts have a negative and significant impact on bank profitability. These findings suggest that banks can improve their profitability through increasing capital size and loan, remaining asset size, deposits, liquidity risk and bad debts reasonably. These findings allow authors to give some solutions to support Vietnam commercial banks increasing their profitability in integration era